The Role of Prices on Excludable Public Goods - Sören Blomquist; Vidar Christiansen (Uppsala University, Department of Economics, 2001)
When a public good is excludable it is possible to charge individuals for using the good. We study the role of prices on excludable public goods within an extension of the Stern-Stiglitz version of the Mirrlees optimal income tax model. Our discussion includes both the case where the public good is a final consumer good and the case where it is an intermediate good. We demonstrate that for a public consumer good charging a positive price may be desirable, but only under certain conditions. However, charging a lower than optimal price may be less efficient than setting a zero price. Conditions are identified under which consumers should be rationed in their demand rather than adjusting demand to price. We also conclude that producers using an intermediate public good as an input should not be charged a positive price.
Keywords: H21; H41; 330; excludable public goods; public sector pricing; information constrained Pareto efficiency; Öffentliche Güter; Einkommensteuer; Optimale Besteuerung; Konsumgut; Vorprodukt; Theorie